Early-Life Factors Are Associated with Vitamin D Status in Early and Mid-Childhood and May Differ between White and Black Children - Switkowski, Karen M (J Nutr, 2021)
BACKGROUND: Suboptimal vitamin D (VitD) status has been associated with poor bone health and other adverse health outcomes and is common among children. Various early-life factors are associated with child VitD, yet few studies have examined multiple factors simultaneously in a single study population. OBJECTIVES: We aimed to characterize relations of early-life factors with plasma 25-hydroxyvitamin D [25(OH)D] concentrations in early and mid-childhood, and to explore potential differences in these associations between white and black children. METHODS: We identified associations of various early-life factors with 25(OH)D concentrations in early and mid-childhood among 961 children in Project Viva using linear regression models. All variables associated with 25(OH)D were included together in final multivariable models at each outcome time point: 1 in the overall sample and additional models for children whose mothers identified them as being white or black. RESULTS: Overall mean ± SD 25(OH)D concentrations were 86 ± 29 nmol/L in early childhood and 68 ± 21 nmol/L in mid-childhood. After accounting for other predictors, children who took VitD supplements (compared with those who did not) had 25(OH)D concentrations 5.6 nmol/L (95% CI: 2.0, 9.2 nmol/L) higher in early childhood and 8.2 nmol/L (95% CI: 4.8, 11.6 nmol/L) higher in mid-childhood. Other factors consistently associated with higher 25(OH)D were blood collection in summer or fall, white race, nonfall birth season, prenatal exposure to higher 25(OH)D, and higher dietary intake of VitD. Greater waist circumference was associated with lower 25(OH)D in early childhood (β: −3.8; 95% CI: −7.4, −0.2 per 1-SD increase) among black children only. CONCLUSIONS: Our findings may help clinicians better target children at risk of lower 25(OH)D for screening and/or intervention and may inform research focused on associations of 25(OH)D with different exposures and outcomes or causal effects of early-life factors on later VitD status. This trial was registered at clinicaltrials.gov as NCT02820402.